Separation of carotene from crude palm oil by membranes - Murugan, C. Sri; Abd. Aziz, Mustafa Kamal; Morad, Noor Azian; S., Micheal (1997)
Malaysia is the world's largest producer and exporter of palm oil. The production figure in 1995 was 7.6 million tonnes and it is anticipated that by the year 2000, the country's production can easily attain 8.8 million tonnes. Palm oil and its products which are exported are in refined, bleached and deodorized forms. This means that thee present refining process in Malaysia causes the destruction of most of the minor components (carotenoids, sterol,tocopherol and tocotrienols) in the crude oil. Membrane applications and research in the edible oil industry are well documented in recent years. Separation of minor components from crude palm by membranes is a new technique. At UTM, research has been initiated to study the possibilities of using membranes to separate carotene from crude palm oil. Preliminary laboratory studies have been conducted by using carotene rich palm olein as the raw sample. A static test cell with effective tested diameter of 22 mm and feed volume of 30ml was used. Two types of new class of solvent stable membranes were determined by using commercial extraction solvents such as hexane and methanol. Optimum operating parameters and conditions which effects the separation performance such as pressure and flux rates have been studied. Initial laboratory investigations have shown encouraging results with 50% separation of the carotene.